2007
DOI: 10.1111/j.1467-9280.2007.01911.x
|View full text |Cite
|
Sign up to set email alerts
|

Lip-Read Me Now, Hear Me Better Later

Abstract: There is evidence that for both auditory and visual speech perception, familiarity with the talker facilitates speech recognition. Explanations of these effects have concentrated on the retention of talker information specific to each of these modalities. It could be, however, that some amodal, talker-specific articulatory-style information facilitates speech perception in both modalities. If this is true, then experience with a talker in one modality should facilitate perception of speech from that talker in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 27 publications
4
34
2
Order By: Relevance
“…This carryover effect may suggest that the talker-specific articulatory information available in the visible mouth can transfer to enhance phonetic convergence to that talker's auditory-only speech. This interpretation would be consistent with previous evidence from our lab illustrating that the learning involved in talker facilitation effects can transfer between modalities (Rosenblum et al, 2007;Sanchez et al, 2013). If visual influences can carry over to affect phonetic convergence to auditory-only stimuli, then we would expect to see such influences in the Experiment 1 noise group that shadowed audiovisual speech prior to shadowing auditory-only speech.…”
Section: Visible Articulation Enhances Phonetic Convergencesupporting
confidence: 89%
“…This carryover effect may suggest that the talker-specific articulatory information available in the visible mouth can transfer to enhance phonetic convergence to that talker's auditory-only speech. This interpretation would be consistent with previous evidence from our lab illustrating that the learning involved in talker facilitation effects can transfer between modalities (Rosenblum et al, 2007;Sanchez et al, 2013). If visual influences can carry over to affect phonetic convergence to auditory-only stimuli, then we would expect to see such influences in the Experiment 1 noise group that shadowed audiovisual speech prior to shadowing auditory-only speech.…”
Section: Visible Articulation Enhances Phonetic Convergencesupporting
confidence: 89%
“…Interestingly, the findings of these two studies showed that the effect of audiovisual training on improving sentence comprehension in noise was independent of the idiosyncrasies of the talker’s articulation, as the talkers in the training and the HINT were not the same. This finding differs from cross-modal studies which have shown that familiarity with the talkers is a key factor in subsequent improvement in auditory speech processing (Rosenblum et al, 2007; von Kriegstein et al, 2008; Wu et al, 2013). Together, it seems that providing audiovisual training materials in a gating format is an efficient short-term approach in improving auditory speech-in-noise identification.…”
Section: Introductioncontrasting
confidence: 99%
“…A growing literature on perceptual learning shows that familiarity with specific voices has wide-ranging effects. These include helping infants isolate words in speech (Houston & Jusczyk, 2000; 2003), improving word perception (Nygaard & Pisoni, 1998; Nygaard et al, 1994; Yonan & Sommers, 2000), improving lip-reading (Rosenblum et al, 2007), changing sublexical processing (Allen & Miller, 2004; Eisner & McQueen, 2005; Kraljic & Samuel, 2005, 2007; Smith & Hawkins, 2012; Sumner, 2011; Sumner & Samuel, 2009; Theodore, Miller & DeSteno, 2009), and improving the ability to segregate overlapping voices (Johnsrude et al, 2013; Newman & Evers, 2007). Indexical variations in speech perception have wide-ranging effects on speech production, the phenomenon of phonetic convergence (or alignment ; Goldinger, 1998; Goldinger & Azuma, 2004; Namy et al, 2004; Nielsen, 2011; Pardo, 2006; Shockley et al, 2004; Smith & Hawkins, 2012).…”
Section: Discussionmentioning
confidence: 99%